The complete chloroplast genome of Wiesnerella denudata (Mitt.) Steph. (Wiesnerellaceae, Marchantiophyta) - Seung Se Choi; Woochan Kwon; Jongsun Park (Mitochondrial DNA. Part B. Resources, 2020)
We completed chloroplast genome of Wiesnerella denudata (Mitt.) Steph, only one species of the monotypic Wiesnerella genus and family Wiesnerellaceae Inoue. It is 122,500 bp and has four subregions: 82,143 bp of large single copy (LSC) and 20,009 bp of small single copy (SSC) regions are separated by 10,174 bp of inverted repeat (IR) regions including 132 genes (88 protein-coding genes, eight rRNAs, and 36 tRNAs). The overall GC content is 28.8% and those in the LSC, SSC, and IR regions are 26.4, 24.6, and 42.8%, respectively. Phylogenetic trees show incongruencies of phylogenetic relationship of W. denudata, requiring additional research.